The Role of Instagram @humas_poldalampung in Disseminating Public Service Announcements - Refi Arioen; Sukamso Sukamso; Marstella Isabela; M. Roby (Penerbit Goodwood, 2025)
Purpose: This study analyzes the role of the Instagram account @humas_poldalampung in Publishing Public Service Announcements (PSAs) and delivering institutional information. It addresses the limited empirical evidence on regional police public relations accounts, particularly whether PSA dissemination is conducted as one-way communication or dialogic engagement. Methodology: A descriptive qualitative approach was used. Data were collected through in-depth interviews with administrators, direct observations, and analyses of archival materials (2022-2024), supported by a literature review. Analysis involved data reduction, coding, thematic categorization, and source triangulation. Results: The content was predominantly informative and educational, covering police activities and PSAs on security, public order, traffic safety, drug prevention, hoax prevention, and public services. Messages were delivered visually through photos, infographics, and short videos. Communication remained largely one-way, with limited sustained interaction. Conclusions: The account functions as a digital public communication channel combining institutional dissemination and persuasive PSAs, but has not fully optimized Instagram for dialogue and participation. This reflects the tension between broadcast-oriented messaging and social media’s dialogic expectations. Limitations: This study focused on one account (2022–2024) without assessing audience perceptions, engagement quality, behavioral impact, or comparing other platforms. Contributions: This study highlights a regional police account and examines PSA dissemination through one-way versus dialogic communication patterns. It offers practical recommendations to improve interaction management, response standards, and structured engagement to enhance trust and PSA effectiveness.